THE INFLUENCE OF HOTEL IMAGE AND TRUST ON GUEST LOYALTY AT GRAND BASKO HOTEL PADANG - Rian Mulawarman; Stephanie Vivian Yuricha; Roni Hermanto; Feri Ferdian (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to determine the effect of hotel image and trust on guest loyalty at Grand Basko Hotel Padang. This research method uses quantitative descriptive research with a causal associative approach, data collected through surveys of guests who have stayed at Grand Basko Hotel Padang using 98 respondents from a population of 7,560 guests staying at Grand Basko Hotel Padang because the sample determination based on the type of non-probability sampling used is purposive sampling technique. Based on the results of data analysis using Smart PLS with the results of Cronbach's each variable 4.245, 9.506 and 4.446 shows that hotel image has a positive and significant effect on guest loyalty, as well as hotel image has a positive and significant effect on trust and trust also has a positive and significant effect on guest loyalty, on the mediating variable hotel image has a direct effect on customer loyalty and indirectly affects customer loyalty through trust as the mediating variable.